2007
DOI: 10.1002/jmv.20955
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of HIV‐1 in Santa Catarina State confirms increases of subtype C in Southern Brazil

Abstract: Recent studies have demonstrated an increased prevalence of human immunodeficiency virus type 1 (HIV-1) subtype C in southern Brazil. Although Santa Catarina State (SC) is located in this area and presents one of the country's highest incidences of HIV/AIDS, knowledge on the molecular epidemiology of HIV-1 in such State is lacking. The aim of this study was to investigate the HIV-1 molecular diversity and epidemiological profile of HIV-1-infected patients from SC. DNA samples were PCR amplified and HIV-1 subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In terms of molecular diversity, our results corroborate previous studies that also reported a large dominance of subtype C (ϳ65%) in SC state (30)(31)(32)(33) and a more diverse epidemic in RS state, mainly because of the high prevalence of BC mosaic forms in the latter (ϳ25%) (34)(35)(36). In both states, a low prevalence of subtype F1 and BF1 recombinants (ϳ3%) was observed, while this frequency can reach up to 20% in northern regions of Brazil (37,38) and 40% in Argentina (39).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of molecular diversity, our results corroborate previous studies that also reported a large dominance of subtype C (ϳ65%) in SC state (30)(31)(32)(33) and a more diverse epidemic in RS state, mainly because of the high prevalence of BC mosaic forms in the latter (ϳ25%) (34)(35)(36). In both states, a low prevalence of subtype F1 and BF1 recombinants (ϳ3%) was observed, while this frequency can reach up to 20% in northern regions of Brazil (37,38) and 40% in Argentina (39).…”
Section: Discussionsupporting
confidence: 91%
“…Subtype C was detected in 25%; other studies analyzing samples from patients of the southern region have observed similarly high prevalences of subtype C 7,8,24,34 . For instance, a study conducted in Santa Catarina (n = 80) reported a high prevalence of subtype C (48.75%), which increased to 71.25% when the recombinant viruses containing subtype C-related sequences were included in the analysis 24 .…”
Section: Discussionmentioning
confidence: 66%
“…For instance, a study conducted in Santa Catarina (n = 80) reported a high prevalence of subtype C (48.75%), which increased to 71.25% when the recombinant viruses containing subtype C-related sequences were included in the analysis 24 . In a study with samples from a voluntary testing site in Curitiba, Paraná, FERREIRA et al 15 detected subtype B in 52.6% of cases, followed by subtype C in 29.8%, mosaic BC in 14%, CF in 1.8%, and F in 1.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since the time of its origin, subtype C has expanded at a faster rate than any other viral subtype. For instance, in southern Brazil, the incidence of subtype C increased from 3% in 1990s (3) to 30% in 2002 (4) and eventually to 45-48% in recent years (5). Furthermore, since the time of their introduction in India, the subtype C strains of India appear to remain genetically stable without undergoing a major genetic recombination with other subtypes, unlike that seen in China or southern Brazil, even though several circulating recombinant forms have been reported from India (6).…”
mentioning
confidence: 99%